The relationship between work facilities, work motivation, and work satisfaction with the performance of non-medical employees at Bhyangkara Level III Hospital Kendari in 2026 - Nur Afdaliah Syam; Siti Rabbani Karimuna; Lade Albar Kalza (PT WIM Solusi Prima, 2026)
Hospitals require optimal human resource performance, both medical and non-medical personnel, to ensure service quality. The performance of non-medical employees at Bhayangkara Level III Hospital Kendari is influenced by various organizational factors such as work facilities, work motivation, and job satisfaction. Initial observations indicate constraints on inadequate work facilities and complaints related to workload that can affect employee motivation and satisfaction. This study aims to determine the relationship between work facilities, work motivation, and job satisfaction with the performance of non-medical employees at Bhayangkara Level III Hospital Kendari in 2026. This type of research is quantitative research with an observational analytical approach and uses a cross-sectional design. The study population was all non-medical employees at Bhayangkara Level III Hospital Kendari, totaling 108 people, with a sample of 84 respondents taken using a simple random sampling technique. Data were collected through questionnaires and analyzed using the Chi-Square statistical test (and the alternative Fisher's Exact Test). The results showed a significant relationship between work facilities and employee performance (p = 0.001) and between work motivation and employee performance (p = 0.005). However, no significant relationship was found between job satisfaction and the performance of nonmedical employees (p=0.120).